2021
DOI: 10.51850/wrj.2020.11.2.48-52
|View full text |Cite
|
Sign up to set email alerts
|

Improving Fire Resistance of Mahogany (Swietenia macrophylla) Wood Impregnated with Mixture of Borax and Boric Acid

Abstract: The study was aimed to investigate the effects of mixture of borax and boric acid concentration and different level of pressure on absorption, retention quantity, and fire resistance properties of mahogany (Swietenia macrophylla). A total of 50 samples of 9 x 19 x 1016 mm (ASTM E 69-02) were taken from mahoganylumber and then air-dried. A total of 45 samples were impregnated with aqueous solutions of borax and boric acid in three different concentrations (5, 7, and 9 %) and at three different pressure levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Boron impregnation has been proven to increase the durability of wood. Compounds frequently used in studies of the mechanical properties of wood are boric acid, borax (Listyanto et al 2020) and disodium octaborate tetrahydrate (Gauss et al 2019). In addition to durability, dimensional stabilization (Demirel et al 2018) and resistance to fire (Lin et al 2020) have also been shown to improve as a result of such treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Boron impregnation has been proven to increase the durability of wood. Compounds frequently used in studies of the mechanical properties of wood are boric acid, borax (Listyanto et al 2020) and disodium octaborate tetrahydrate (Gauss et al 2019). In addition to durability, dimensional stabilization (Demirel et al 2018) and resistance to fire (Lin et al 2020) have also been shown to improve as a result of such treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the properties of wood, e.g., its combustibility, dimensional stability, and biodeterioration must be managed for practical use. To mitigate these disadvantageous characteristics, numerous wood preservatives have been developed.Boric acid, phosphoric acid, and their salts are known to enhance the fire resistance of wood or wood-based materials [1][2][3][4][5][6][7][8][9][10][11][12][13] . Treatments with colloidal silicate 14,15 or metal oxides via sol-gel processes [16][17][18][19][20][21][22][23][24][25] have also been reported to endow wood-inorganic composites with fire-resistant properties.It has been demonstrated that acetylation and formalization are effective techniques for improving the dimensional stability of wood [26][27][28] .…”
mentioning
confidence: 99%
“…Boric acid, phosphoric acid, and their salts are known to enhance the fire resistance of wood or wood-based materials [1][2][3][4][5][6][7][8][9][10][11][12][13] . Treatments with colloidal silicate 14,15 or metal oxides via sol-gel processes [16][17][18][19][20][21][22][23][24][25] have also been reported to endow wood-inorganic composites with fire-resistant properties.…”
mentioning
confidence: 99%